Première alerte sur le Saulchoir (1932) - Fouilloux, Étienne (Revue des sciences philosophiques et théologiques, 2012)
The opening of the Holy Office’s archives, under Pius XI’s pontificate, shows that a first warning was issued against the Saulchoir House of Studies in 1932. Denounced by two student brothers, it became the target of an investigation, the answers to which shed light on the divergences at the heart of the “great thomist family”. This investigation led to a mistrial exactly at the time when the Saulchoir received the visit of the General Chapter of the Order who granted one of the suspected professors, Father Marie-Dominique Chenu, a Master’s degree in theology, who was thus immediately appointed the House rector.